An inertial triple-projection algorithm for solving the split feasibility problems - DANG, Yazheng (Institutional Knowledge at Singapore Management University, 2023)
This paper proposes a new inertial triple-projection algorithm for solving the split feasibility problem (SFP).The process of projections is divided into three parts. Each part adopts a different variable stepsize to obtain its projection point, which is different from the existing extragradient methods. Flexible rules are employed for selecting the stepsizes and the inertial technique is used for improving the convergence. Convergence results are proven. Numerical experiments show that the proposed method converges more quickly than the general CQ algorithm.